Parkinson’s disease-implicated kinases in the brain; insights into disease pathogenesis - Dzamko, Nicolas; Zhou, Jinxia; Huang, Yue; Halliday, Glenda M. (Frontiers in Molecular Neuroscience, 2014)
Substantial evidence implicates abnormal protein kinase function in various aspects of Parkinson’s disease (PD) etiology. Elevated phosphorylation of the PD-defining pathological protein, α-synuclein, correlates with its aggregation and toxic accumulation in neurons, whilst genetic missense mutations in the kinases PTEN-induced putative kinase 1 (PINK1) and leucine-rich repeat kinase 2 (LRRK2), increase susceptibility to PD. Experimental evidence also links kinases of the phosphoinositide 3-kinase (PI3K) and mitogen-activated protein kinase (MAPK) signaling pathways, amongst others, to PD. Understanding how the levels or activities of these enzymes or their substrates change in brain tissue in relation to pathological states can provide insight into disease pathogenesis. Moreover, understanding when and where kinase dysfunction occurs is important as modulation of some of these signaling pathways can potentially lead to PD therapeutics. This review will summarize what is currently known in regard to the expression of these PD-implicated kinases in pathological human postmortem brain tissue.